Cholesterol modulates acetylcholine receptor diffusion by tuning confinement sojourns and nanocluster stability - Mosqueira, Alejo (2018)
Fil: Mosqueira, Alejo. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Neurobiología Molecular; Argentina